(3JCKjQ GdYeGQI GdQbejI GdJaGYdjI Ydi GdJUeje GdOGNdi ddeJGMa GdCKQjI(B/s - (3CejQI GdSjO YHO GdYXje s ([(3O(B.(3e(B]:s [(3O(B.(3f(B](3,s, 2014)
(3jTJed Ydi edNU HGddZJjf GdYQHjI hGdCfLdjRjI (B.s
(3GdeQGLY ef U (B(470-477).s
(3OQLI GdeGLSJjQ (B-(3cdjI Gdafhf GdJWHjbjI (B,2014.s
Keywords: (3GdJUeje GdeYeGQi (B-(3GdeJGMa GdCKQjI (B.s